Knowledge of the nursing team of a long stay institution regarding care for elderly patients with Alzheimer in the municipality of Vitória da Conquista - Bahia (Research, Society and Development, 2022)
Alzheimer's disease presents itself as a form of dementia that affects the elderly and greatly compromises their physical, mental and social integrity, resulting in the need for increasingly complex care. The present work proposes to verify the knowledge of the nursing team of a long-stay institution regarding the care of the elderly with Alzheimer's, guided by the questioning of the knowledge of the nursing team regarding the care of the elderly with Alzheimer's. This is an exploratory, descriptive, cross-sectional study with a qualitative approach, carried out among nursing professionals, including nurses, nursing technicians and nursing assistants, working within a Long Stay Intuition for the elderly, in the municipality of Vitória da Conquista - BA. The socio-economic-demographic conditions of the participants were investigated through a qualitative analysis, and according to the Bardin model, the knowledge of Nursing professionals regarding AD, as well as the way in which they apply Nursing care were evaluated. It appears that the nursing team has knowledge about the needs inherent in the care of patients with AD It was possible to conclude that there is a need for nursing to have technical-scientific knowledge to perform the necessary and specific care for patients patients with AD, thus favoring the distinction of complications and allowing the planning of care strategies. The research respected the ethical precepts contained in resolutions nº 466/12 and 510/2016 of the National Health Council.